2016
DOI: 10.1103/physrevb.94.075131
|View full text |Cite
|
Sign up to set email alerts
|

Variational Monte Carlo study of chiral spin liquid in quantum antiferromagnet on the triangular lattice

Abstract: By using Gutzwiller projected fermionic wave functions and variational Monte Carlo technique, we study the spin-1/2 Heisenberg model with the first-neighbor (J 1 ), second-neighbor (J 2 ), and additional scalar chiral interaction J χ S i · (S j × S k ) on the triangular lattice. In the nonmagnetic phase of the J 1 -J 2 triangular model with 0.08 J 2 /J 1 0.16, recent density-matrix renormalization group (DMRG) studies [Zhu and White, Phys. Rev. B 92, 041105(R) (2015) and Hu, Gong, Zhu, and Sheng, Phys. Rev. B … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
42
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 78 publications
(126 reference statements)
3
42
0
Order By: Relevance
“…It would be interesting to investigate the nature of the phase transitions from the tetrahedral [8] and the 120 • Néel phases into the CSL. Finally a recent purely variational study [49] also found evidence for a CSL in our model for selected values of J 2 and J χ .…”
supporting
confidence: 71%
See 1 more Smart Citation
“…It would be interesting to investigate the nature of the phase transitions from the tetrahedral [8] and the 120 • Néel phases into the CSL. Finally a recent purely variational study [49] also found evidence for a CSL in our model for selected values of J 2 and J χ .…”
supporting
confidence: 71%
“…The groundstate of this tight binding model at half filling is given by filling the orbitals of the lower band. After Gutzwiller projection such a state has been shown to yield a CSL wavefunction [7,10,48,49]. To construct the topological partner of the CSL wavefunction the phases in the tight-binding model before projection can be tuned such that locally the flux through each triangle remains π/2 while the flux through incontractible loops around the torus changes.…”
mentioning
confidence: 99%
“…We note that recent numerical work using density matrix renormalization group (DMRG) and variational Monte Carlo methods supports the existence of a region of spin liquid in a J1 − J2 Heisenberg model on a triangular lattice where the next nearest neighbor (NNN) J2 is in the range 0.08 < J2/J1 < 0.15 (32)(33)(34)(35)(36). Currently, many groups find it difficult to distinguish between the Z 2 spin liquid, the chiral spin liquid, and the U (1) Dirac spin liquid.…”
Section: Possible Spin Liquid States In Tasmentioning
confidence: 99%
“…The effective nearest-neighbor exchange constants are given in Eq. (28). All other couplings and the constant contri-…”
Section: Discussionmentioning
confidence: 99%